1 OPTIMASI PENGGUNAAN SUMBER DAYA USAHATANI SAYURAN (HORTIKULTURA) POLA TUMPANGSARI - muhidin m Sirat (Jurnal Ekonomi Pembangunan, 2018)
The objectives of this research were to find out whether tomato and chili intercrop farming in Rulung Sari village had reached a production level with optimal outcomes, whether the use of that farming resource had been optimal, and whether there were income improvement in the farming by using simplex method. The data used in this study is primary data. This was a quantitative research to estimate the optimization of farming income outcome. This research used linear programming by using simplex method and QM for Windows V3 software for analyses. The estimation results showed that the tomato and chili farming production by using intercropping in Rulung Sari village did not yet reach optimal outcome. The optimal outcomes for tomato and chili productions were Rp. 60,840,696 and Rp. 110,117,028 respectively. The optimization model estimation result showed that the use of farming resource was not yet optimal and it showed that there would be outcome improvement by using simplex method.